2019
DOI: 10.1590/1414-462x201900030237
|View full text |Cite
|
Sign up to set email alerts
|

Necessidades de crianças com síndrome congênita pelo Zika vírus no contexto domiciliar

Abstract: Resumo Introdução Famílias de crianças com Zika vírus têm se deparado com diversas demandas relacionadas ao cuidado com a criança, no domicílio e na vida social. Objetivo Compreender a dinâmica familiar e a promoção de cuidados à criança com síndrome congênita do Zika vírus no contexto domiciliar. Método Estudo qualitativo, do qual participaram oito famílias de crianças com síndrome congênita do Zika vírus. Foram realizadas entrevistas semiestruturadas por meio de visita domiciliar. Resultados Emergiram tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 24 publications
(28 reference statements)
0
12
0
9
Order By: Relevance
“…28 29 Our study has demonstrated that the lack of trained professionals to support families is a major issue for parents that needs to be addressed. 30 Furthermore, parents expressed a great need for information about the condition of their children. 31 The Centers for Disease Control and Prevention has produced a pocket guide summarising paediatric guidelines on initial assessment and outpatient treatment for CZS.…”
Section: Discussionmentioning
confidence: 99%
“…28 29 Our study has demonstrated that the lack of trained professionals to support families is a major issue for parents that needs to be addressed. 30 Furthermore, parents expressed a great need for information about the condition of their children. 31 The Centers for Disease Control and Prevention has produced a pocket guide summarising paediatric guidelines on initial assessment and outpatient treatment for CZS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, uncertainties about functional limitations, future implications and demands for care to come, still under study (9) . Due to the great possibility of severe limitations of cognition and motor skills, there is a need for coordinated and family-centered health care (9)(10) . There is evidence that family-centered care for children with special needs has better results (11) .…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, care for children with CZVS must be multi-professional to support the family in comprehensive care for the child's biological, psychological and social development. In addition to the daily family care to meet their needs related to functional limitations, it includes early stimulation in the family care routine (10,12) . Early stimulation, especially in the first years of life, a period in which brain development occurs more quickly, maximizes the potential for physical growth and neurological, behavioral, cognitive, affective and social maturation (12) .…”
Section: Introductionmentioning
confidence: 99%
“…Em geral, essa população apresentava graves danos no desenvolvimento neuropsicomotor (Brunoni et al, 2016), sendo descritos riscos para sequelas como atraso motor, hipertonia, deformidades e contraturas de membros, e paralisia cerebral (PC) (Brunoni et al, 2016;Marques et al, 2019;Pessoa et al, 2018), impactando desfavoravelmente na participação em atividades como o brincar, nos diferentes ambientes, como o domiciliar (Duarte et al, 2019); levando a limitações na capacidade funcional e na qualidade de vida individual e familiar (Brunoni et al, 2016).…”
Section: Introductionunclassified